Literature Review on Green Finance and Corporate Green Innovation - Xu, Yijie (Transactions on Economics, Business and Management Research, 2024)
Under the background of "dual-carbon" strategy, how green finance can help enterprises’ green innovation and promote social transformation has become a key issue. This paper compiles the literature on green finance and enterprise green innovation at home and abroad in the form of literature review, summarizes the definition, development history and indicator measurement methods of green finance and enterprise green innovation, outlines the economic consequences of green finance and the influencing factors of enterprise green innovation, and based on the theoretical foundations adopted by scholars at home and abroad, and sums up the impacts and mechanisms of green finance on enterprise green innovation. It is found that most scholars believe that green finance can actively promote enterprise green innovation. In terms of the mechanism of action, this paper concludes that green finance can promote corporate green innovation by alleviating financing constraints, increasing the proportion of long-term debt and alleviating the shortage of funds, etc. Differences in enterprise size, pollution level, ownership and external regional intellectual property rights will lead to different degrees of influence of green finance on corporate green innovation. In response to the above findings, this paper proposes future research directions for green finance and corporate green innovation, with a view to providing help and insights for the effective promotion of corporate green innovation and the development and improvement of the theoretical framework of green innovation.